Pembuatan Tong Sampah Dalam Meningkatkan Kualitas Hidup Di Desa Karya Indah Kabupaten Kampar - Marpaung, Noveri Lysbetti; Sukma, Dian Yayan; Nurhalim, Nurhalim; Hutabarat, Sakti; Ervianto, Edy (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Rubbish is items that are no longer used by their owners and are typically discarded. Improperly managed or burned waste can have significant negative impacts. Environmental pollution is one of the main consequences of waste that is carelessly disposed of leading to contamination. Accumulated waste becomes a breeding ground for diseases, such as mosquito and rat infestations, which can carry various illnesses that affect humans. This situation can negatively impact the quality of life and the hygienist of the environment surrounding the waste. Therefore, it is essential to have a container to collect waste in Karya-Indah-Village to maintain a hygienic environment and protect the health of the people living nearby. This Community Service’s purpose is to provide rubbish-bins at the public service facility in Karya-Indah-Village. This activity has received full support from the village authorities. The availability of rubbish-bins, hopefully, will increase public awareness of the negative impacts and dangers of waste and waste burning on health, as well as enhance the community's concern for the environment and health. Thus, the Community Service Team from the University of Riau, together with MBKM Kukerta Unri students, has provided rubbish-bins in Karya-Indah-Village to improve the quality of life in the village.